2021
DOI: 10.1080/1034912x.2021.1895975
|View full text |Cite
|
Sign up to set email alerts
|

Tiered Approaches to Rehabilitation Services in Education Settings: Towards Developing an Explanatory Programme Theory

Abstract: Rehabilitation services in education settings are evolving from pullout interventions focused on remediation for children and youth with special education needs to inclusive whole-school tiered approaches focused on participation. A limited number of discipline-specific practice models for tiered services currently exist. However, there is a paucity of explanatory theory. This realist synthesis was conducted as a first step towards developing a middlerange explanatory theory of tiered rehabilitation services i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 104 publications
(168 reference statements)
2
17
0
Order By: Relevance
“…However, the unique nature of MdlV as well as the positive results of the present study in terms of participants' interest and perceived benefits warrant future studies seeking to clarify the mechanisms of action and effects of this intervention. A future realist evaluation using data from internal documents related to the development and implementation of this activity, from the perspective of stakeholders (e.g., participants, facilitators) and from peer-reviewed studies of similar interventions, would allow to generate an explanatory theory of this innovation which could be further tested (29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…However, the unique nature of MdlV as well as the positive results of the present study in terms of participants' interest and perceived benefits warrant future studies seeking to clarify the mechanisms of action and effects of this intervention. A future realist evaluation using data from internal documents related to the development and implementation of this activity, from the perspective of stakeholders (e.g., participants, facilitators) and from peer-reviewed studies of similar interventions, would allow to generate an explanatory theory of this innovation which could be further tested (29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies emphasized the necessity of inter-organizational commitment of leaders in education and health to facilitate the conditions needed for a systematic, coordinated approach to the adoption of evidence-based service delivery models and frameworks (Anaby et al, 2019;Missiuna & Hecimovich, 2015;Phoenix et al, 2021;VanderKaay et al, 2021). This was a point of consensus among participants of the current study; however, it was beyond the scope of this study to explore the extent to which leaders held common definitions related to tiered or integrated services, for example, universal, targeted and intensive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers suggested that the adoption of evidence-based service delivery models requires the inter-organizational commitment of leaders in both education and health. It also requires a systematic, coordinated approach to address the provision of training, time to meet, and monitoring and evaluation of service outcomes for and with children and families (Anaby et al, 2019;Missiuna & Hecimovich, 2015;Phoenix et al, 2021;VanderKaay et al, 2021). A realist synthesis conducted by Van-derKaay et al (2021)…”
Section: Resounding Calls For Leadership Actionmentioning
confidence: 99%
“…However, some modifications were suggested for the categories of tiered interventions to present the interventions considering students` outcomes. Thus, a recent framework on tiered approaches to rehabilitation by VandeKaay et al [19] proposing different categories aiming different therapy outcomes was used to guide the creation of categories for tiered interventions. The research team also identified additional categories for some interventions that could not be attributed to any of the proposed categories within the guiding framework (e.g., increased quality of life and health).…”
Section: Analysis and Analysis Processmentioning
confidence: 99%
“…An agreement was reached in the previous round Liaise with school-based occupational therapist to plan skill training Modified as "Liaise with other service providers (e.g., occupational therapists, speech therapist) and other school team members (e.g., special education teachers, learning support team) to plan skill training" Developing a transition plan with families (e.g., transition from primary school to secondary school) for students with motor impairments Modified as "Developing a transition plan with the family, student and school personnel (e.g., transition from primary school to secondary school) for students with motor impairments" Collaborating with orthotists, outpatient PTs/OTs and AT specialists to meet the needs of students 91% ✓ Collaborating with or coaching school personnel (e.g., educators, learning support team) to address the needs of students regarding14) setting educationally relevant goals and collaboratively plan on how to promote students` learning and achievement 15) balance, coordination, and strength 16) accommodations and individualized strategies for a child with a disability 17) adaptive equipment and its use for a student to maximize functions of students18) adapting activities in a gym or classroom to foster the participation of a child with a disability19) mobility of the students in the schools (e.g., classroom, bathroom, playground) 20) postural support and positioning of students during school activities (e.g., positioning of a student with dysphagia at lunch or sitting ergonomics) 21) creating a maximal stimulating environment for students with motor impairment 22) physical activity program for students23) learning new methods or ways to support a student in need24) safe manual handling of a students at school (e.g., in and out of a chair, stander or walker)25) equipment acquisition, modification, trails, adjustment and repair 26) fall prevention strategies 27) compensation strategies for students with motor impairment 28) orthotic support management 29) accommodations and individualized strategies for a student returning to school after an injury or surgery (return-to-school protocol) Facilitating inclusion of students with disabilities in PE class and other activities in the school 96% ✓ Collaborating with or coaching families to address the needs of children regarding: 32) setting educationally relevant goals and collaboratively plan on how to promote students` learning and achievement 33) accommodations and individualized strategies for a student with a disability 34) orthotic support and an exercise program for students who need orthotic support such as cerebral palsy, pes planus, etc. 35) a maximal stimulating environment for students with motor impairment 36) compensation strategies for a student with motor impairment 37) understanding what can be done at home to help the student function better in school 38) learning new methods or ways to support the student in need 39) physical activity programs for students 40) assistive devices for students with motor impairment 41) accommodations and individualized strategies for a child returning to school after an injury/surgery Strengthening the child's agency-as being agents to overcome environmental barriers at school 91% ✓ 46) Implementing appropriate activities of daily living (ADL) strategies into school routine to facilitate student access and participation of student with special needs in student activities 91% ✓ 47) Supporting equipment acquisition, modification, adjustment and repair to enhance the functioning of a student in in school, home and community 87% ✓ 48) Getting in...…”
mentioning
confidence: 99%